PENGARUH TERAPI RELAKSASI GUIDED IMAGERY TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Yudi Abdul Majid (IKesT Muhammadiyah Palembang, 2021)
Background: The elderly are individuals aged 60 years and over who experience physical, mental, psychosocial changes. One of the thysical changes in the cardiovaskular system where the heart valves thicken and become stiff so that the aortic wall decreases. The heartꞌs ability to pump blood decreases resulting in loss of elasticity of blood vessels which can cause blood pressure which is at risk for several degenerative disease including hypertension. Hypertension is a condition in which a person experiences an increase in blood pressure above normal. One of the non-farmakological treatments is guided imagery relaxation theraphy, guided imagery relaxation theraphy is a techique that uses a personꞌs imagination by imagining good or happy things, fun and calming. Research Objectives: The aim in this study was to analyze the effect of guided imagery relaxation theraphy on blood pressure in the elderly with hypertension. Research Methods: This study uses a literature review by analyzing articels related to the research. Data were obtained from electronic databases, namely Goggle Scholar, Pubmed, Proques, with the keywords elderly, guided imagery, and hypertension published in 2015-2020. Results: Based on the results of the analysis of 10 research articles reviewed, it was found that area there was a significant effect of guided imagey relaxation theraphy on changes in blood pressure in the elderly with hypertension, because by stimulating the brain through imagination, a response in the nervouse system can arise which makes the body relax. It is felt by the body so that endorphins are released into the blood vessels so that the blood vessels experience vasodilation and the blood supply is fulfilled which can cause a decrease in blood pressure and heart rate. Conclussion: Guided imagery relaxation theraphy can reduce blood pressure in elderly patients with hypertension.